The witching moon manor : a novel - Sivinski, Stacy (The spellbound sisters, 2025)
"The Quigley sisters return to the Crescent Moon Tearoom to bargain with Fate once more in the sequel to Stacy Sivinski's Nationally Bestselling debut, The Crescent Moon Tearoom"--